Cell-cycle control of cell polarity in yeast - Moran, Kyle D; Kang, Hui; Araujo, Ana V; Zyla, Trevin R; Saito, Koji; Tsygankov, Denis; Lew, Daniel J (The Journal of cell biology, 2019)
In many cells, morphogenetic events are coordinated with the cell cycle by cyclin-dependent kinases (CDKs). For example, many mammalian cells display extended morphologies during interphase but round up into more spherical shapes during mitosis (high CDK activity) and constrict a furrow during cytokinesis (low CDK activity). In the budding yeast , bud formation reproducibly initiates near the G1/S transition and requires activation of CDKs at a point called "start" in G1. Previous work suggested that CDKs acted by controlling the ability of cells to polarize Cdc42, a conserved Rho-family GTPase that regulates cell polarity and the actin cytoskeleton in many systems. However, we report that yeast daughter cells can polarize Cdc42 before CDK activation at start. This polarization operates via a positive feedback loop mediated by the Cdc42 effector Ste20. We further identify a major and novel locus of CDK action downstream of Cdc42 polarization, affecting the ability of several other Cdc42 effectors to localize to the polarity site.